Diffraction of Н-polarised photons on the infinite grating of metallic ribbons - Безуглий, А.В.; Петченко, О.М. (Radiotekhnika, 2019)
The problem diffraction of H-polarized photons at the normal incidence of stream on a grate, formed an unlimited sequence infinitely thin metallic ribbons, was solved in the given paper. A problem about determination of ψ-function of photon before and behind of grating is reduced to the boundary value problem of Reeman Gilbert. Exact expressions are got for ψ-function as the endless system of algebraic equations. Calculations are performed using approximate formulas for some values of the parameters.